Risk factors for early periventricular intraventricular hemorrhage in extremely low birth weight infants: a retrospective study - Yueju Cai; Yongjiang Jiang; Ping Wang; Xiaopeng Zhao; Yanyan Song; Xiaolan Li (BMC Pediatrics)
Abstract Background This study aimed to explore the risk factors for early intraventricular hemorrhage (IVH) in extremely low birth weight infants (ELBWIs) to provide guidance for early intervention, thereby improving survival rates and quality of life for these vulnerable infants. Methods A retrospective study was conducted on 205 ELBWIs admitted to the Women and Children’s Medical Center of Guangzhou Medical University from January 2019 to December 2023. Standard head ultrasound screening (HUS) was used to assess the presence and severity of IVH on days 1–3 and 5–7 post-birth. Infants were categorized into either the IVH or non-IVH group based on HUS findings. Univariate analysis and logistic regression were employed to identify risk factors for IVH, and the efficacy of the model was evaluated using a receiver operating characteristic (ROC) curve. Results Among the 205 ELBWIs (97 males, 108 females), 82 (40%) developed IVH, with 26 (12.7%) classified as severe IVH and 56 (27.3%) as mild IVH. IVH within the first three days occurred in 51 of the 82 cases. Severe IVH was more prevalent in the lower gestational age groups: 40.0% in infants at 23 + 1 to 26 weeks, 10.7% in infants at 26 + 1 to 28 weeks, and 1.4% in infants at 28 + 1 to 32 weeks (p < 0.001).Logistic regression analysis revealed two independent risk factors: failure to withdraw invasive ventilation within the first week (OR = 3.276, 95% CI = 1.465–7.324, p = 0.004) and the use of vasoactive drugs within the first week (OR = 2.112, 95% CI = 1.002–4.451, p = 0.049). The ROC curve showed a sensitivity of 68.3%, specificity of 81.3%, and an area under the curve (AUC) of 0.792. Conclusion The incidence of IVH in ELBWIs is high, particularly within the first three days after birth. The use of vasoactive drugs and prolonged invasive ventilation are associated with increased risk, highlighting the need for careful management of respiratory and hemodynamic support in these infants.